Pelatihan Pengelolaan Keuangan Keluarga & Menciptakan Usaha Kreatif Pembuatan Es Sago Melon Pada Ibu-Ibu Dharma Wanita - Iip Dyah Kusumaningati; Umi Mas’ulah; Didi Hermawan (LP3M Universitas Putra Bangsa, 2024)
The aim of this service activity is to produce services that can be adopted by Dharma Wanita mothers in the form of knowledge about how to manage family finances, which includes knowledge about planning family financial expenditure, knowledge about implementing family financial management, and knowledge about assessment, supervision of family finances, as well as Empowering Dharma Wanita mothers by providing examples of creative businesses that can be carried out, namely making Sago Melon Ice. This community service activity was carried out in Kramat District, Tegal Regency after activities were carried out at the regular meeting of the Dharma Wanita Association of KWK Dikbud which was attended by approximately 40 participants. The method of implementing Community Service regarding Family Financial Management Training & Creating Creative Businesses Making Sago Melon Ice for Dharma Wanita Women, KWK Dikbud Association, Kramat District, Tegal Regency, is by using several methods, namely the lecture method, discussion method (question and answer), management training method family finances, guidance methods, and practical methods for making sago melon ice.